Some Recollections of the Radio and Electrical Engineering Division of the National Research Council of Canada, 1946-1977 - Covington, Arthur (Scientia Canadensis, 1991)
AbstractStudies of extraterrestrial radio noise became world wide after WWII, and were rapidly separated into a number of disciplines. Solar radio astronomy, at a wavelength of 10.7 cm, was initiated in 1946 at the Radio Field Station of the National Research Council. Its development at the Goth Hill Radio Observatory outside Ottawa is outlined until 1962, when the work was transferred to the Algonquin Radio Observatory.